PENGETAHUAN WANITA USIA SUBUR TENTANG KEPUTIHAN FISIOLOGIS DAN PATOLOGIS DI PUSKESMAS SUMBANG II KECAMATAN SUMBANG KABUPATEN BANYUMAS TAHUN 2010 - Afri Julianingsih; Maya Safitri; Indri Heri S (Viva Medika, 2010)
Background: The problem of whiteness is a problem that has long been a problem forwomen. In a world of ever experiencing vaginal discharge about 75%. In Indonesiathe number of affected WUS whiteness as much as 23.53 million people, in the DistrictDonates likelihood of discharge as much as 11 669 people.Objective: To determine the knowledge overview of women of childbearing age aboutthe physiological and pathological whiteness in Puskesmas Sumbang II DistrictBanyumas.Methods: This research method is quantitative descriptive based on primary datataken using a questionnaire with a sample size 87. The sampling technique accidentalsampling.Results: Respondents have less knowledge about the physiological and pathologicalvaginal discharge most that 33 respondents (37.9%). Most respondents have SMP /MTs / equal and have sufficient knowledge as much as 50%. Most of the respondentswho obtained the information from a friend and as much as 44.7% of them have lessknowledge. Most respondents have a life of 20-29 years and 36.8% of them have lessknowledge. Most respondents have jobs IRT and 52.5% of them have less knowledgeabout the physiological and pathological vaginal discharge. And all respondentsexperiencing vaginal discharge as many as 87 respondents (100%), of which 37.9%were mempuyai less knowledge.Conclusion: Most of WUS in Puskesmas Sumbang II District Banyumas have lessknowledge about the physiological and pathological vaginal discharge.Keywords: Knowledge, WUS, Physiological vaginal discharge, vaginal dischargePathological.